Full‐Solution Processed Flexible Organic Solar Cells Using Low‐Cost Printable Copper Electrodes. (15th September 2014) - Li, Kan; Zhen, Hongyu; Niu, Liyong; Fang, Xu; Zhang, Yaokang; Guo, Ruisheng; Yu, You; Yan, Feng; Li, Haifeng; Zheng, Zijian
<x xml:space="preserve">Abstract</x> Full‐solution‐processed flexible organic solar cells (OSCs) are fabricated using low‐cost and high‐quality printable Cu electrodes, which achieve a power conversion efficiency as high as 2.77% and show remarkable stability upon 1000 bending cycles. This device performance is thought to be the best among all full‐solution‐processed OSCs reported in the literature using the same active materials. This printed Cu electrode is promising for application in roll‐to‐roll fabrication of flexible OSCs. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>